2023
DOI: 10.1038/s41380-023-02167-z
|View full text |Cite
|
Sign up to set email alerts
|

Adult-born neurons maintain hippocampal cholinergic inputs and support working memory during aging

Abstract: Adult neurogenesis is reduced during aging and impaired in disorders of stress, memory, and cognition though its normal function remains unclear. Moreover, a systems level understanding of how a small number of young hippocampal neurons could dramatically in uence brain function is lacking. We examined whether adult neurogenesis sustains hippocampal connections cumulatively across the life span. Long-term suppression of neurogenesis as occurs during stress and aging resulted in an accelerated decline in hippoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that neurons undergoe a progressive decline in functionality with age, resulting in a memory and cognition decline. 6 Aging is the leading risk factor for neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease. 7 As post-mitotic cells, senescent neurons, similar to other post-mitotic cells, exhibit senescent features such as increased SA-β-gal activity and enhanced expression of γH2AX and p16, rather than cell-cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that neurons undergoe a progressive decline in functionality with age, resulting in a memory and cognition decline. 6 Aging is the leading risk factor for neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease. 7 As post-mitotic cells, senescent neurons, similar to other post-mitotic cells, exhibit senescent features such as increased SA-β-gal activity and enhanced expression of γH2AX and p16, rather than cell-cycle arrest.…”
Section: Introductionmentioning
confidence: 99%